Ethnobotanical study of wild edible plants traditionally used by the inhabitants of Lalku Valley, District Swat, Pakistan - Ali Shah , Sayed Haidar; Mujtaba Shah, Ghulam; Rehman, Sabith; Ali, Niaz; Alam, Jan; Waheed, Fareeha; Ali, Farhat; Hussain, Wahid (Ethnobotany Research and Applications, 2025)
Background: The non-cultivated edible plants are collected by local people from the surrounding environment and used in various food recipes. The relationship of human communities with such plants has been considered an ecological balance system since ancient times. Much ethnobotanical research has proven the importance of wild edible plants for the local communities, especially in emergency like war, famine, and drought. Methods: An ethnobotanical study was conducted in 26 villages/ settlements of Lalku Valley, district Swat to document the wild edible plants used as food by local inhabitants. The data was collected using group discussions and oral face-to-face interviews through semi-structured questionnaires. The related information was collected from 222 local informants (179 males and 43 females). Informants were told about the study's aims and Prior Informed Consent was obtained. The acquired data was analyzed through various statistical indices like Use Reports (UR), and Relative Frequency of Citation (RFC). Results: A total of 60 plant species belonging to 31 families and 46 genera were reported as wild edible plants (WEPs) traditionally used in the study area. Rosaceae was reported as the dominant plant family with 10 species followed by Lamiaceae 5 while Amaranthaceae and Moraceae with 3 species each. Herbs were reported as the most widely used form with 29 species (48.33%), followed by shrubs with 14 species (23.33%), trees with 12 species (20.00%), and climbers with 2 species (3.33%). Fruits were the most widely used part with 24 species (40.00%), Young shoot with 23 species (39.65%), Leaf with 16 species (26.66%), Seeds and whole plant used with 4 species (6.66%) each, flower with 2 species (3.33%) while bulb and corm with 1 species each (1.66%). Among them, 34 species (56.66%) were consumed uncooked, and 26 species (43.3%) were cooked before consumption. Based on the availability of plants, 26 wild edible plant species are available and collected in the summer season (May-August), 21 species in the spring- early summer season (April- May), and 12 species in the autumn season (September-November). Conclusions: The local people have rich knowledge related to wild edible plants (WEPs).The results show a strong relationship between the local communities with wild edible plants (WEPs) species which is a potential source to ensure food security. Further studies are required to document and preserve such traditional knowledge. Keywords: Wild edible plant, Ethnobotany, Traditional knowledge, Relative Frequency of Citation (RFC)